2018
DOI: 10.1088/1674-4926/39/12/122003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precursor solution concentration on the structural, optical and humidity sensing properties of spray-deposited TiO2thin films

Abstract: In the present paper, the influence of precursor concentration on the structural, optical, and humidity sensing properties of spray-deposited titanium dioxide (TiO2) films are investigated. The TiO2 thin films were successfully deposited by spraying different precursor concentrations such as 0.075 M, 0.1 M, and 0.125 M of titanium trichloride solution onto glass substrates. X-ray diffractometry (XRD) studies confirmed the polycrystalline anatase phase of TiO2 with dominant (101) plane. The crystallite size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
2
2
0
Order By: Relevance
“…RH% varies inversely with humidity and fits exactly with the equation Y=100 / X. This result coincides with that obtained by Gapale et al [15]. This group found that the resistance of TiO 2 decreased exponentially with the increasing of RH%.…”
Section: -2-2 Humidity Sensingsupporting
confidence: 91%
See 1 more Smart Citation
“…RH% varies inversely with humidity and fits exactly with the equation Y=100 / X. This result coincides with that obtained by Gapale et al [15]. This group found that the resistance of TiO 2 decreased exponentially with the increasing of RH%.…”
Section: -2-2 Humidity Sensingsupporting
confidence: 91%
“…Iraqi Journal of Science, 2019, Vol. 60, No.8, pp: 1894-1703 58;; Lower sensitivity of the TiO 2 sensor at low RH% values can be attributed to the filling of larger sized pores with water vapor and then the condensation of them on its walls resulting in the filling of all empty areas of the pores [15].…”
Section: Khaleel and Hashimmentioning
confidence: 99%
“…Specifically, the band gap values decreased from 3.38 eV to 3.26 eV. This observation is consistent with the findings reported in prior studies, 39,40 indicating a convergence of results. The reduction in the band gap associated with elevated deposition rates can be ascribed to the spatial confinement of electrons and holes, leading to energy level quantization.…”
Section: Resultssupporting
confidence: 92%
“…The concentration of surface charge carriers is an important factor that can affect the amount of absorbed water vapour on the surface of the samples [34,35] and can be tuned by varying concentration of dopants in the pristine TiO 2 . The conduction mechanism in chemisorbed and first physisorbed layer can be ascribed to the tunnelling of electrons, while the conduction at the second physiosorbed layer is protonic conduction or the Grotthuss conduction mechanism [36] . The second physiosorbed layer is always in equilibrium with the atmospheric humidity.…”
Section: Humidity Sensing Propertiesmentioning
confidence: 99%